A snake venom ophthalmia: A case – report: Poster Presentation - Case Report - Resident - Aljufri, Nabila; Sadikin, Irma Suwandi; Petra, Dany; Susantono, Diannisa; Oktariani, Virna Dwi; Widyawati, Syska (Majalah Oftalmologi Indonesia, 2023)
Introduction : Snake venom ophthalmia is caused by venoms of spitting snakes. Delayed treatment may result in corneal ulcer, corneal perforation and blindness. We aim to report a fortunate snake venom ophthalmia case. Case Illustration : A-54-year-old male complained of burning eye pain, watery, and redness of the right eye (RE) after being spat by a snake 3 hours before admission. The snake was identified as a cobra-snake, spitted at a distance of 1 meter without body bite. He rinsed his eyes with tap water and irrigated at a nearby hospital before referred. During the admission, the pH of both eyes (BE) was 8. The patient was irrigated with normal-saline. The visual acuity (VA) of the right eye was 6/12 and left eye 6/6. There was RE conjunctival and ciliary injection. Other examinations were unremarkable. The patient was discharged and treated with levofloxacin eye-drop, sulfas-atropine 1%, EDTA 1%, artificial tears, and vitamin C. He did self-eye irrigation. Two days later, he presented with VA of 6/6 for BE with normal ocular examinations and pH of 7 for BE. Discussion : The general principle is prompt and copious irrigation of the eyes in chemical contact. The snake venom mixture of chemicals was washed out, which local necrosis can be prevented. Managing snake venom as a chemical splash injury with considerable irrigation, lubricants, and topical antibiotics, resulted a good outcome and prevented sequelae in this patient. Conclusion : Urgent irrigation of the affected eyes and other mucous membranes is the key in treating snake venom ophthalmia